Do Mechatronic Poles Change the Gait Technique of Nordic Walking in Patients with Ischemic Heart Disease? - Agnieszka Szpala; Sławomir Winiarski; Małgorzata Kołodziej; Bogdan Pietraszewski; Ryszard Jasiński; Tadeusz Niebudek; Andrzej Lejczak; Dariusz Kałka; Karolina Lorek; Krzysztof Bałchanowski; Sławomir Wudarczyk; Marek Woźniewski (Applied Bionics and Biomechanics)
The study aimed to compare the technique of normal gait with the Nordic walking (NW) gait with classical and mechatronic poles in patients with ischemic heart disease. It was assumed that equipping classical NW poles with sensors enabling biomechanical gait analysis would not cause a change in the gait pattern. The study involved 12 men suffering from ischemic heart disease (age: 66.2 ± 5.2 years, body height: 173.8 ± 6.74 cm; body mass: 87.3 ± 10.89 kg; disease duration: 12.2 ± 7.5 years). The MyoMOTION 3D inertial motion capture system (Noraxon Inc., Scottsdale, AZ, USA) was used to collect biomechanical variables of gait (spatiotemporal and kinematic parameters). The subject’s task was to cover the 100 m distance with three types of gait-walking without poles (normal gait), walking with classical poles to NW, and walking with mechatronic poles from the so-called preferred velocity. Parameters were measured on the right and left sides of the body. The data were analyzed using two-way repeated measures analysis of variance with the between-subject factor “body side.” Friedman’s test was used when necessary. For most kinematic parameters, with the exception of knee flexion–extension (p=0.474) and shoulder flexion–extension (p=0.094), significant differences were found between normal and walking with poles for both the left and right side of the body and no differences due to the type of pole. Differences between the left and right movement ranges were identified only for the ankle inversion–eversion parameter (gait without poles p=0.047; gait with classical poles p=0.013). In the case of spatiotemporal parameters, a reduction in the cadence step value using mechatronic poles and the stance phase using classical poles compared to normal walking was observed. There was also an increase in the values for step length and step time regardless of the type of poles, stride length, and swing phase when using classical poles and stride time when using mechatronic poles. The differences between the right and left sides of the measurement occurred when walking with both types of poles for single support (gait with classical poles p=0.003; gait with mechatronic poles p=0.030), stance phase (gait with classical poles p=0.028; gait with mechatronic poles p=0.017) and swing phase (gait with classical poles p=0.028; gait with mechatronic poles p=0.017). Mechatronic poles can be used in the study of the biomechanics of gait in real-time with feedback on its regularity because no statistically significant differences were found between the NW gait with classical and mechatronic poles in the studied men with ischemic heart disease.